2016
DOI: 10.1038/ncomms12801
|View full text |Cite
|
Sign up to set email alerts
|

Optical manipulation of single flux quanta

Abstract: Magnetic field can penetrate into type II superconductors in the form of Abrikosov vortices, which are magnetic flux tubes surrounded by circulating supercurrents often trapped at defects referred to as pinning sites. Although the average properties of the vortex matter in superconductors can be tuned with magnetic fields, temperature or electric currents, handling of individual Abrikosov vortices remains challenging and has been demonstrated only with sophisticated scanning local probe microscopies. Here we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 30 publications
2
92
0
Order By: Relevance
“…Taking J c = 0.7 × 10 6 A/cm 2 which is relevant to the samples in Ref. [46] we find that f p ∼ 10 pN/μm. Thus, to neglect the vortex attraction to the sample boundaries one needs F att f p t, which is realized for |y v − w| 0.2w ∼ 300 nm.…”
Section: Optically Controlled 0-π Transitions In Thin Planar Josementioning
confidence: 99%
See 4 more Smart Citations
“…Taking J c = 0.7 × 10 6 A/cm 2 which is relevant to the samples in Ref. [46] we find that f p ∼ 10 pN/μm. Thus, to neglect the vortex attraction to the sample boundaries one needs F att f p t, which is realized for |y v − w| 0.2w ∼ 300 nm.…”
Section: Optically Controlled 0-π Transitions In Thin Planar Josementioning
confidence: 99%
“…Recently it was experimentally demonstrated that the position of a single Abrikosov vortex can be controlled by the tip of the magnetic force microscope [43,44], the electron beam [41], the probe of the scanning tunneling microscope [45], or the focused laser beam [46]. The latter technique allows the ultrafast optically controlled positioning of an individual Abrikosov vortex which opens a new avenue for the design of novel optoelectronic superconducting devices.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations